Towards reconsideration of the intersection of the charter right to freedom of expression and copyright in Canada - Reynolds, G (2015)
This thesis explores the intersection of freedom of expression (as protected in the Canadian Charter of Rights and Freedoms (Charter)) and copyright in Canada. In this thesis, I argue that both lower Canadian courts and the Supreme Court of Canada (SCC) should reconsider their approaches to this intersection. Lower Canadian courts have consistently rejected arguments that provisions of Canada's Copyright Act unjustifiably infringe the Charter right to freedom of expression. The SCC, on the other hand, has consistently interpreted provisions of the Copyright Act in such a manner as to result in expanded protection for the expression interests of non-copyright owning parties. It has done so not by relying explicitly on the Charter right to freedom of expression, but through a process of statutory interpretation. I argue that both approaches merit reconsideration. Specifically, I argue that the approaches adopted by lower Canadian courts to the intersection of the Charter right to freedom of expression and copyright are based on now-invalidated approaches to both copyright and to freedom of expression, and are thus themselves invalid; that to the extent to which the SCC's approach to this intersection assumes that the Charter right to freedom of expression can be protected, in the context of copyright, through statutory interpretation alone, that it fails to adequately protect the Charter right to freedom of expression; that other leading national courts from which the SCC has previously sought assistance have explicitly engaged with this intersection, and that the SCC should follow suit; and that the SCC's own copyright and freedom of expression jurisprudence suggests that provisions of the Copyright Act may unjustifiably infringe the Charter right to freedom of expression. These four arguments, taken together, suggest that the time is ripe for reconsideration of this intersection.